The Ash Wednesday Supper - Bruno, Giordano, 1548-1600 (Lorenzo da Ponte Italian library., 2018)
"Giordano Bruno wrote this dialogue in 1583. The Ash Wednesday Supper is concerned with two major themes: a cosmological theme concerning the new post Copernican astronomy and Bruno's infinitist reading of it; and the other a social/historical theme concerning the english society, both high and low, of which Bruno was a guest and with which he developed a complex and often conflictual relationship."--